Efficacy of Corneal Collagen Cross-Linking for the Treatment of Keratoconus: A Systematic Review and Meta-Analysis. Issue 3 (March 2016) - Meiri, Zohar; Keren, Shay; Rosenblatt, Amir; Sarig, Tal; Shenhav, Liat; Varssano, David
Abstract : Purpose: To examine the efficacy of corneal collagen cross-linking (CXL) for the treatment of keratoconus (KCN). Methods: A systemic literature review and meta-analysis of ocular functional and structural parameters of patients with KCN undergoing cross-linking procedures were performed using PubMed and the web of science. A literature search was performed for relevant peer-reviewed publications on population-based studies. Data were analyzed with R software (Meta library), and heterogeneity was assessed with the Cochran Q and I 2 . A random-effects model was used for high heterogeneity; otherwise a fixed model was used. Sensitivity analysis of particular tested groups was used to explain high heterogeneity. The main outcome measures extracted from the articles were corrected distance visual acuity, uncorrected distance visual acuity, and maximum K. Results: An improvement in visual acuity of 1 to 2 Snellen lines was found 3 months or more after undergoing CXL. Changes were more pronounced in uncorrected visual acuity. Some topography parameters were found to be improved (0.6–1 diopters) 12 to 24 months after CXL. The refractive cylinder improved by 0.4 to 0.7 diopters. Endothelial cell density decreased by 225 cells per square millimeter in the first 3 months and thereafter returned to normal. Corneal thickness was reduced by 10 to 20 μm in the year following CXL but not after 24 months. No changes in intraocular pressure were noted. Conclusions: CXL is a safe and effective method for halting the deterioration of KCN, while slightly improving visual function. Abstract : Supplemental Digital Content is Available in the Text.